Prediction of response and survival after standardized treatment with 7400 MBq 177Lu-PSMA-617 every 4 weeks in patients with metastatic castration-resistant prostate cancer - Rasul, Sazan; Hartenbach, Markus; Wollenweber, Tim; Kretschmer-Chott, Elisabeth; Grubmüller, Bernhard; Kramer, Gero; Shariat, Shahrokh; Wadsak, Wolfgang; Mitterhauser, Markus; Pichler, Verena; Vraka, Chrysoula; Hacker, Marcus; et al. (European journal of nuclear medicine and molecular imaging, 2021)
BACKGROUND AND AIMS: [177Lu]Lu-PSMA-617 radioligand therapy (PSMA-RLT) is a new therapy for patients with metastatic castration-resistant prostate cancer (mCRPC). However, identification of reliable prognostic factors is hampered by heterogeneous treatment regimens applied in previous studies. Hence, we sought clinical factors able to predict response and survival to PSMA-RLT in a homogenous group of patients, all receiving 7400 MBq every 4 weeks. PATIENTS AND METHODS: Data of 61 patients (mean age 71.6 ± 6.9 years, median basal PSA 70.7 [range 1.0-4890 μg/L]), pretreated with abiraterone/enzalutamide (75.4%) and docetaxel/cabazitaxel (68.9%), received three cycles of PSMA-RLT (mean 7321 ± 592 MBq) at four weekly intervals and were analyzed retrospectively. General medical conditions and laboratory parameters of every patients were regularly assessed. Response to therapy was based on PSA levels 1 month after the 3rd cycle. Binary logistic regression test and Kaplan-Meier estimates were used to evaluate predictors and overall survival (OS). RESULTS: Forty-nine (80.3%) patients demonstrated a therapy response in terms of any PSA decline, while 21 (19.7%) patients showed increase or no changes in their PSA levels. Baseline hemoglobin (Hb) significantly predicted PSA reductions of ≥ 50% 4 weeks after receiving the 3rd PSMA-RLT (P = 0.01, 95% CI: 1.09-2.09) with an AUC of 0.68 (95% CI: 0.54-0.81). The levels of basal Hb and basal PSA were able to predict survival of patients, both P < 0.05 (relative risk 1.51 and 0.79, 95% CI: 1.09-2.09 and 0.43-1.46), respectively. In comparison to patients with reduced basal Hb, patients with normal basal Hb levels lived significantly longer (median survival not reached vs. 89 weeks, P = 0.016). Also, patients with basal PSA levels ≤ 650 μg/L had a significantly longer survival than patients with basal PSA levels > 650 μg/L (median survival not reached vs. 97 weeks, P = 0.031). Neither pretreatments with abiraterone/enzalutamide or docetaxel/cabazitaxel nor distribution of metastasis affected survival and rate of response to PSMA-RLT. CONCLUSION: Basal Hb level is an independent predictor for therapy response and survival in patients receiving PSMA-RLT every 4 weeks. Both baseline PSA ≤ 650 μg/L and normal Hb levels were associated with longer survival.
Keywords: výsledek terapie; Male; retrospektivní studie; Dipeptides; Radiopharmaceuticals; heterocyklické sloučeniny monocyklické; Aged; mužské pohlaví; senioři; Prostatic Neoplasms, Castration-Resistant; nádory prostaty rezistentní na kastraci; Treatment Outcome; radiofarmaka; lidé; Heterocyclic Compounds, 1-Ring; Humans; dipeptidy; Retrospective Studies; lidé středního věku; Middle Aged